Development of Reverse Transcription Loop-Mediated Isothermal Amplification Assay for Rapid and On-Site Detection of Avian Influenza Virus - Golabi, Mohsen; Flodrops, Marion; Grasland, Beatrice; Vinayaka, Aaydha C.; Quyen, Than Linh; Nguyen, Trieu; Bang, Dang Duong; Wolff, Anders (Frontiers in Cellular and Infection Microbiology, 2021)
Avian influenza virus (AIV) outbreaks occur frequently worldwide causing potential public health risk and large economic losses to poultry industries. Considering the high mutation rate and frequent genetic reassortment between segments in the genome of AIVs, emerging new strains are a real threat that may infect and spread through human population causing a pandemic. Therefore, rapid AIV diagnostic tests are essential tools for surveillance and assessing virus spreading. Real-time reverse transcription PCR (rRT-PCR) targeting matrix gene is the main official standard test for AIV detection but the method requires well-equipped laboratories. Reverse transcription Loop-Mediated Isothermal Amplification (RT-LAMP) has been reported as a rapid method and an alternative to PCR in pathogen detection. The high mutation rate in AIV genome increases the risk of false negative in nucleic acid amplification methods of detection such as PCR and LAMP due to possible mismatch priming. In this study, we analyzed 800 matrix gene sequences of newly isolated AIV in EU and designed a highly efficient LAMP primer set that covers all AIV subtypes. The designed LAMP primer set was optimized in real-time RT-LAMP (rRT-LAMP) assay. The rRT-LAMP assay detected AIV samples belongs to 9 various subtypes with the specificity and sensitivity comparable to the official standard rRT-PCR assay. Further, a two-color visual detection RT-LAMP assay protocol was adapted with an aim to develop on-site diagnostic test. The on-site testing successfully detected spiked AIV in birds oropharyngeal and cloacal swabs samples at a concentration as low as 100.8 EID50 per reaction within 30-minutes including sample preparation. The results revealed a potential of this newly developed rRT-LAMP assay to detect AIV in complex samples using a simple heat treatment step without the need for RNA extraction.